(untitled) (Sains Humanika, 2018)
The development of waqf institutions is a significant attribution to ensure a sustainable and progressive prosperity to the Muslim socio-economic. The aspiration of the waqf development is to preserve the benefits of the beneficiaries and to all the human kind. However, the issues of the fund shortage are one of the tough issues that need to be solved. I-REIT (Islamic Real Estate Investment Trust) is one of a suggestion of diversification as an alternative solution to the aspect of fund constraint. Therefore, this paper attempts to examine the level of I-REIT volatility in comparison to typical REIT as a preliminary experiment. By using a conventional standard deviation or variance analysis of selected I-REIT and REIT counter, a preliminary result shows that I-REIT has a lower volatility impact than the REIT. This less-impact I-REIT to the market exploitation justifies that the Islamic capital market instruments of Islamic real estate investment trust (I-REIT) is an alternative potential waqf mechanism in developing and advancing waqf property in Malaysia. Thus, this study proposes the initiation of the alternative waqf of I-REIT in enhancing the dynamism of waqf practice in Malaysia. Â